Regulation of Aegilops tauschii Coss Tiller Bud Growth by Plant Density: Transcriptomic, Physiological and Phytohormonal Responses - Yu, Haiyan; Cui, Hailan; Chen, Jingchao; Li, Xiangju (Frontiers in Plant Science, 2020)
Aegilops tauschii Coss is one of the most hazardous weeds that severely infests wheat fields in China. The tillering ability of Ae. tauschii strongly affects the occurrence and spread by influencing its seed output. In this study, Ae. tauschii was sown at low plant density (LPD) and high plant density (HPD) to investigate the effect of plant density on tiller bud outgrowth and its intrinsic regulatory mechanism using RNA-Seq. Additionally, the chlorophyll content and photosynthesis, soluble sugar and phytohormone levels were also determined at different plant densities. The results showed that an increased plant density significantly inhibited the elongation of tiller buds in the axil of the first leaf at 15 days after planting, with 7.69 mm at LPD and 1.69 mm at HPD. A total of six putative tiller-related genes were selected and validated using quantitative real-time PCR. Furthermore, the expression of most differentially expressed genes (DEGs) involved in chlorophyll biosynthesis and photosynthesis was distinctly inhibited by HPD, which agreed with the decreased chlorophyll levels and low photosynthetic efficiency at HPD. Similar results were also detected for soluble sugar. In addition, DEGs were markedly enriched in indole-3-acetic acid (IAA), abscisic acid (ABA), and gibberellin metabolism and signaling. Accordingly, the levels of ABA and gibberellin acid 3 in Ae. tauschii were strikingly higher at HPD compared with those at LPD, yet the reverse tendency was observed for IAA. Undoubtedly, such results will be highly beneficial for illuminating the mechanism of the Ae. tauschii tillering response to plant density and will provide new ideas for the control of this weed in the future.